2012
DOI: 10.3402/rlt.v20i0.18976
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to the digital age: a narrative approach

Abstract: The article adopts a narrative inquiry approach to foreground informal learning and exposes a collection of stories from tutors about how they adapted comfortably to the digital age. We were concerned that despite substantial evidence that bringing about changes in pedagogic practices can be difficult, there is a gap in convincing approaches to help in this respect. In this context, this project takes a “bottom-up” approach and synthesises several life-stories into a single persuasive narrative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although the previously mentioned studies for investigating SM used many different research approaches, narratives are not often encountered. One of the studies (Cousins and Bissar 2012) revealed the reflections on experiences of lecturers using the digital technology. This was performed by listening to the referred lecturers' life stories.…”
Section: Analysing the Experiences On Sm Use For Educational Purposesmentioning
confidence: 99%
“…Although the previously mentioned studies for investigating SM used many different research approaches, narratives are not often encountered. One of the studies (Cousins and Bissar 2012) revealed the reflections on experiences of lecturers using the digital technology. This was performed by listening to the referred lecturers' life stories.…”
Section: Analysing the Experiences On Sm Use For Educational Purposesmentioning
confidence: 99%
“…We believe that while there is an intensive use of Web 2.0 and social media in education especially in higher education, there is a need to discover and understand lecturers' stories regarding integration of social media into their way of teaching and their students learning outside the classroom walls. One such research conducted [15] aimed to understand faculty reflections during the process of adapting digital technologies by listening to their life stories.…”
Section: The Reason and Context For Using Narrativementioning
confidence: 99%
“…In narrative forms, educators can creatively probe their practice, their commonalities, and differences in a deeper way (Langer, 2016). By telling stories, academics might reflect on their teaching and attitudes to educational technology (Cousins & Bissar, 2012). The process of creating a shared account of work encourages creativity, but also collegiality and community (Vallis & Lopomo Beteto, in press).…”
Section: Introductionmentioning
confidence: 99%